Multi-scale system reliability analysis of lifeline networks under earthquake hazards. - Song, Junho (Earthquake engineering & structural dynamics.)
Recent earthquake events evidenced that damage of structural components in a lifeline network may cause prolonged disruption of lifeline services, which eventually results in significant socio-economic losses in the affected area. Despite recent advances in network reliability analysis, the complexity of the problem and various uncertainties still make it a challenging task to evaluate the post-hazard performance and connectivity of lifeline networks efficiently and accurately. In order to overcome such challenges and take advantage of merits of multi-scale analysis, this paper develops a multi-scale system reliability analysis method by integrating a network decomposition approach with the matrix based system reliability (MSR) method. In addition to facilitating system reliability analysis of large size networks, the multi-scale approach enables optimizing the level of computational effort on subsystems; identifying the relative importance of components and subsystems at multiple scales; and providing a collaborative risk management framework. The MSR method is uniformly applied for system reliability analyses at both the lower scale (for link failure) and the higher scale (for system connectivity) to obtain the probability of general system events, various conditional probabilities, component importance measures, statistical correlation between subsystem failures and parameter sensitivities. The proposed multi-scale analysis method is demonstrated by its application to a gas distribution network in Shelby County of Tennessee. A paremetric study is performed to determine the number of segments during the lower scale MSR analysis of each pipeline based on the strength of the spatial correlation of seismic intensity. It is shown that the spatial correlation should be considered at both scales for accurate reliability evaluation. The proposed multi-scale analysis approach provides an effective framework of risk assessment and decision support for lifeline networks under earthquake hazards.